A prospective, observational study on conversion of clinically isolated syndrome to multiple sclerosis during 4-year period (MS NEO study) in Taiwan. - Long-Sun Ro (PLoS ONE, 2019)
Importance CIS to MS conversion rates vary depending on population cohorts, initial manifestations, and durations of follow-up. Objective To investigate conversion rate of patients from CIS to MS and the prognostic significance of demographic and clinical variables in Taiwanese population. Design Nationwide, prospective, multi-centric, observational study from November 2008 to November 2014 with 4 years follow-up. Setting Multi-centre setting at 5 institutions in Taiwan. Participants 152 patients having single clinical event potentially suggestive of MS in last 2 years were enrolled as consecutive sample. 33 patients were lost to follow-up and 16 patients did not complete the study.103 patients completed the study. Intervention(s) (for clinical trials) or exposure(s) (for observational studies) Natural progression from first episode of CIS to MS or NMO was observed. Main outcome(s) and measure(s) Variables analysed were 'proportion of patients converting to MS or NMO after first episode of CIS', 'duration between first episode of neurological event and diagnosis of MS', 'status of anti-AQP4 IgG' and 'length of longest contiguous spinal cord lesion in MS patients'. Association between baseline characteristics and progression to MS from CIS was analyzed using multiple logistic regression. Multivariate time dependent effect of baseline characteristics on progression to MS was plotted. Results 14.5% patients with CIS converted to MS after 1.1 ± 1.0 years with greater predisposition (18.8%) in those having syndromes referable to the cerebral hemispheres. Conversion rate from ON to MS was 9.7%. 90.9% patients had mild disease course. 46.7% patients had abnormal MRIs at baseline, with 0.6±0.5 contrast enhanced lesions. 'Below normal BMI' and 'MRI lesion load (≥ 4 lesions)' were identified as risk indicators for the development of MS. Amongst the patients who developed NMO as diagnosed by modern criteria, 80% were positive for anti-AQP4 IgG antibody. Conclusions and relevance 'Below normal BMI' and 'number of demyelinating lesions (≥4)' are significant predictors of conversion from CIS to MS. A low conversion rate to MS in Taiwanese CIS patients and majority of them having a mild course and minimal disability suggest the roles of geographic, genetic and ethnic factors. Trial registration Non-trial observational study.